Herbicide Resistance: Another Hot Agronomic Trait for Plant Genome Editing - Amjad Hussain; Xiao Ding; Muna Alariqi; Hakim Manghwar; Fengjiao Hui; Yapei Li; Junqi Cheng; Chenglin Wu; Jinlin Cao; Shuangxia Jin (Plants, 2021)
Weeds have continually interrupted crop plants since their domestication, leading to a greater yield loss compared to diseases and pests that necessitated the practice of weed control measures. The control of weeds is crucial to ensuring the availability of sufficient food for a rapidly increasing human population. Chemical weed control (herbicides) along with integrated weed management (IWM) practices can be the most effective and reliable method of weed management programs. The application of herbicides for weed control practices calls for the urgency to develop herbicide-resistant (HR) crops. Recently, genome editing tools, especially CRISPR-Cas9, have brought innovation in genome editing technology that opens up new possibilities to provide sustainable farming in modern agricultural industry. To date, several non-genetically modified (GM) HR crops have been developed through genome editing that can present a leading role to combat weed problems along with increasing crop productivity to meet increasing food demand around the world. Here, we present the chemical method of weed control, approaches for herbicide resistance development, and possible advantages and limitations of genome editing in herbicide resistance. We also discuss how genome editing would be effective in combating intensive weed problems and what would be the impact of genome-edited HR crops in agriculture.